Does androgen‐ablation therapy (AAT) associated autophagy have a pro‐survival effect in LNCaP human prostate cancer cells?. (16th August 2012) - Bennett, Haley L.; Stockley, Jacqueline; Fleming, Janis T.; Mandal, Ranadip; O'Prey, Jim; Ryan, Kevin M.; Robson, Craig N.; Leung, Hing Y.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Androgen‐ablation therapy (AAT) and chemotherapy are commonly used to treat incurable prostate cancer. To improve outcome, there is major on‐going research to develop more effective treatments with less toxicity. Autophagy has been suggested from previous studies to play a potential role in cell survival and may be associated with resistance to chemotherapy. Autophagy is known to be upregulated by nutrient starvation or AAT in prostate cancer. However, its functional impact is not fully known. The present study describes the potential synergism between the blockade of autophagy and AAT alone or AAT combined with taxane chemotherapy. Hence, future combined treatment options are warranted to further investigate the clinical impact of autophagy suppression as a treatment strategy. Objective To study the cellular effects of the anti‐androgen bicalutamide on autophagy and its potential impact on response to androgen‐ablation therapy (AAT) alone or combined with docetaxel chemotherapy in human prostate cancer LNCaP cells. Materials and Methods LNCaP cells were treated with bicalutamide ± docetaxel, and cellular effects were assayed: lipidated LC3 (a microtubule‐associated protein) for autophagy and its trafficking to fuse with lysosome; flow cytometry using propidium iodide or caspase 3 for cell death; and sulforhodamine B assay for cell growth. Results Bicalutamide treatment enhanced autophagy in LNCaP cells with increased level of autophagosome coupled with an altered cellular morphology reminiscent of neuroendocrine differentiation. Consistent with the literature on the interaction between androgen receptor activation and taxane chemotherapy, bicalutamide diminished docetaxel mediated cytotoxicity. Significantly, pharmacological inhibition of autophagy with 3‐methyladenine significantly enhanced the efficacy cell kill mediated by AAT ± docetaxel. Conclusion Autophagy associated with bicalutamide treatment in LNCaP cells may have a pro‐survival effect and strategy to modulate autophagy may have a potential therapeutic value.